"My French is rusty": Proficiency and bilingual gesture use in a majority English community. Issue 4 (August 2019) - AZIZ, JASMINE R.; NICOLADIS, ELENA
Abstract : Gestures serve many functions, including aiding language access and message construction, particularly in spatial tasks. Some researchers have argued that gesture frequency is linked to proficiency in bilinguals, although results have been inconsistent. We tested Nicoladis' (2007 ) proposal that bilinguals' proficiency interacts with task: namely, more spatial tasks elicit greater proficiency effects. French–English bilinguals completed a cartoon-retell task (high spatial) and an interview task (low spatial) in both languages. We measured bilingual proficiency categorically by first language (L1) and continuously by assessing receptive vocabulary, oral fluency, and word types. Participants gestured more in the cartoon-retell task, but there were minimal proficiency effects and no interactions between proficiency and task. Interestingly, only participants with English as their L1 gestured more in their second language (L2), potentially due to 'rustiness', or lexical access difficulties in French from low usage in the majority English community.